2016
DOI: 10.1016/j.ajic.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, source of information, and perception of Portuguese medical students and junior doctors of infection control precautions

Abstract: Medical education should include infection control precautions (ICPs). Portuguese medical students showed reasonable knowledge in ICPs; however, contact isolation and glove and mask use should be reinforced. Only 25% referred to the curriculum as the most important information source. There was a positive association between academic year (P = .032), previous training in ICPs (P = .016), and knowledge. Main strategies proposed to acquire competences in ICPs were bedside teaching (26.9%) and curriculum and beds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
3
4
0
Order By: Relevance
“…The current COVID-19 pandemic has led to a greater use of PFRs among healthcare workers than previously, and identified a need for more training in PPE skills [ 27 ]. The knowledge deficit identified in this study aligns with that of Peres et al [ 28 ], in which surveys of advanced medical students and junior doctors found that 59% of respondents had inadequate knowledge about PPE. Potential self-contamination, due to errors in PPE doffing, has been demonstrated in a number of studies which has implications for pathogen transmission not only to clinicians, themselves, but also to the environment and patients [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…The current COVID-19 pandemic has led to a greater use of PFRs among healthcare workers than previously, and identified a need for more training in PPE skills [ 27 ]. The knowledge deficit identified in this study aligns with that of Peres et al [ 28 ], in which surveys of advanced medical students and junior doctors found that 59% of respondents had inadequate knowledge about PPE. Potential self-contamination, due to errors in PPE doffing, has been demonstrated in a number of studies which has implications for pathogen transmission not only to clinicians, themselves, but also to the environment and patients [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…The current COVID-19 pandemic has led to a greater use of N95/P2 respirators among healthcare workers than usual, which has identi ed a need for training in PPE skills (25). The knowledge de cit identi ed in this study aligns with that of Peres et al (26), in which surveys of advanced medical students and junior doctors found that 59% of respondents had inadequate knowledge about PPE. Potential self-contamination, due to errors in PPE do ng, has been demonstrated in a number of studies which has implications for pathogen transmission not only to clinicians, themselves, but also to the environment and patients (27,28).…”
Section: Discussionsupporting
confidence: 86%
“…Healthcare professionals, including physicians, dentists, or nurses and student healthcare, while full-time pharmacists have not existed until now. [19][20][21][22] The clinical pharmacist specialized in infection control was suggested as one specialized clinical pharmacist in the pharmacy strategic plan with updated vision 2030 as an infection control pharmacist. 23 The American Society of Heath system pharmacist stated the pharmacist's role in the Antimicrobial Stewardship and infection control performances as combined in one specialty.…”
Section: Introductionmentioning
confidence: 99%